Biomacromolecule/lipid hybrid nanoparticles for controlled delivery of sorafenib in targeting hepatocellular carcinoma therapy. (April 2017) - Zhang, Jing; Wang, Tianqi; Mu, Shengjun; Olerile, Livesey D; Yu, Xiaoyue; Zhang, Na
Aim: Hybrids composed of various materials are highly versatile for drug delivery in tumor therapy including hepatocellular carcinoma. Herein, a sorafenib (SF)-loaded biomacromolecule hyaluronic acid (HA)/lipid hybrid nanoparticles (HA/SF-cLNS) were developed for targeting drug delivery.Materials & methods: In vitro assays determined HA/SF-cLNS release behavior, enzymatic degradation, uptake and cytotoxicity. H22-bearing liver cancer xenograft murine models were used to evaluate the biodistribution and therapeutic efficacy in vivo .Results: HA/SF-cLNS could be disassembled and drug was released in response to hyaluronidase. In vivo imaging results demonstrated HA/cLNS could enhance drug accumulation at tumor site. Meanwhile, HA/SF-cLNS exhibited improved antitumor efficacy in vitro and in vivo .Conclusion: HA/SF-cLNS demonstrated the potential to enhance antitumor efficacy of SF.